Analysis of risk factors and prevention strategy in accidents among coal hauling trucks: a scoping review - Adenan, Adenan; Djunaidi, Zulkifli (Intelektual Pustaka Media Utama, 2025)
Powered hauling equipment is one of the most critical operational elements in the mining sector. Haulage is a significant hazard for the mining industry, accounting for over half of all mining-related fatal accidents yearly. Identifying safety risk variables is the foundation of risk assessment and accident prevention. This study aimed to identify risk variables and prevention techniques to reduce occurrences among truck drivers in coal mining. This research approach is a scoping review with the PRISMA Extension for Scoping Reviews (PRISMA-ScR). Thirty-five articles were reviewed based on the results of inclusion and exclusion criteria. Data analysis was performed using content analysis. The results show that human, environmental, machine and organizational factors contribute to the risk among truck drivers in coal mining. Safety culture, staffing and scheduling, training and education, policy and procedure implementation, and technology deployment are all part of the accident prevention plan. The central government should pay particular attention to the employment conditions of workers in cities with decreased resources and develop policies to prevent mining-related diseases in local communities.